1998
DOI: 10.1021/jp980559+
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Magnetic Interaction in Organic Radical Crystals. 3. Galvinoxyl Radicals in 1-D Crystals,

Abstract: Using the band theory, the nature of the spin exchange interaction between the unpaired electrons within the half-filled band of 1-D organic radical crystals, consisting of galvinoxyl radicals, is investigated theoretically. The various contributions to the Heisenberg effective exchange integral, J eff , the direct, kinetic, and indirect spin exchange, are evaluated quantitatively for the experimentally determined crystal structure. To establish the dependence of J eff on the crystal topology and geometry, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This species has attracted interest because of it exceptional stability (it can be isolated in pure form and is essentially insensitive to oxygen) and its unusual solid state magnetic properties. 86 Computational studies show that, like simple phenoxyls, there is substantial spin density on the para carbon atoms in 34, leading to an alternate representation of galvinoxyl and related species 87 as delocalized allyl-type radicals 35. 88 Closely related to 34 is "Yang's biradical" 36, 89 a stable triplet (S = 1) diradical.…”
Section: Phenoxyl Radicalsmentioning
confidence: 99%
“…This species has attracted interest because of it exceptional stability (it can be isolated in pure form and is essentially insensitive to oxygen) and its unusual solid state magnetic properties. 86 Computational studies show that, like simple phenoxyls, there is substantial spin density on the para carbon atoms in 34, leading to an alternate representation of galvinoxyl and related species 87 as delocalized allyl-type radicals 35. 88 Closely related to 34 is "Yang's biradical" 36, 89 a stable triplet (S = 1) diradical.…”
Section: Phenoxyl Radicalsmentioning
confidence: 99%
“…A huge number of compounds with magnetic properties containing metals or metal complexes are known and used everywhere in science and industry . However, only a few pure organic compounds possessing magnetic properties are known, and their critical temperatures are not higher than several Kelvins. The compounds suitable for the synthesis of organic materials with magnetic properties are stable radicals that build structures with transitional symmetry with unpaired electrons in their elementary units (EUs). , 1D stacks of PAHs are promising candidates for such materials. , Not so long ago the synthesis of large PAHs seemed out of reach, and they were used only as theoretical models. In a recent paper, a new synthetic concept for the synthesis of huge PAHs and their derivatives was introduced .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The compounds suitable for the synthesis of organic materials with magnetic properties are stable radicals that build structures with transitional symmetry with unpaired electrons in their elementary units (EUs). 1,[14][15][16][17][18] 1D stacks of PAHs are promising candidates for such materials. 19,20 Not so long ago the synthesis of large PAHs seemed out of reach, and they were used only as theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…The stacks of the molecular crystals are found to be ϳ13.9 Å wide with an intermolecular distance inside these stacks along the c axis of roughly 0.65 nm 3 . Furthermore, the distance of about 3.71 Å between the carbon atoms of two adjacent molecules 22 is relatively high compared to distances found in stacks of other radicals. Nevertheless, the typical -interaction is presumed.…”
Section: Introductionmentioning
confidence: 75%
“…21 The nature of the spin exchange interaction between the unpaired electrons has been described using the band model. 22 In order to understand the mechanism of the magnetic interactions, ferromagnetic properties like spin population, spin arrangement and the spontaneous magnetic moment per molecule have been calculated by ab initio studies. 23 It was found that the total DOS below the Fermi level exhibits sharp peaks, i.e., energy bands below the Fermi level are narrow and flat.…”
Section: Introductionmentioning
confidence: 99%